Long-Term Costs of Maximum Nonoperative Treatments in Patients With Symptomatic Lumbar Stenosis or Spondylolisthesis that Ultimately Required Surgery: A 5-Year Cost Analysis. Issue 6 (15th March 2019) - Adogwa, Owoicho; Davison, Mark A.; Vuong, Victoria D.; Khalid, Syed; Lilly, Daniel T.; Desai, Shyam A.; Moreno, Jessica; Cheng, Joseph; Bagley, Carlos
Abstract : Study Design: Retrospective cohort study. Objective: The purpose of this study is to characterize the utilization and costs of MNTs prior to spinal fusion surgery in patients with symptomatic lumbar stenosis or spondylolisthesis. Summary of Background Data: The costs and utilization of long-term maximal nonoperative therapy (MNT) can be substantial, and in the current era of bundled payments, the duration of conservative therapy trials should be reassessed. Methods: A large insurance database was queried for patients with symptomatic lumbar stenosis or spondylolisthesis undergoing index lumbar decompression and fusion procedures between 2007 and 2016. This database consists of 20.9 million covered lives and includes private/commercially insured and Medicare Advantage beneficiaries. Only patients with lumbar stenosis or spondylolisthesis and those continuously active within the insurance system for at least 5 years prior to the index operation were eligible. Results: A total of 4133 out of 497, 822 (0.8%) eligible patients underwent 1, 2, or 3-level posterior lumbar instrumented fusion. 20.8% of patients were smokers, 44.5% had type II DM, and 38.2% were obese (body mass index [BMI] >30 kg/m 2 ). Patient MNT utilization was as follows: 66.7% used nonsteroidal anti-inflammatory drugs (NSAIDs), 84.4% used opioids, 58.6% used muscle relaxants, 65.5% received lumbar epidural steroid injections (LESI), 66.6% attended 21.1% presented to the emergency department (ED), and 24.9% received chiropractor treatments. The total direct cost associated with all MNT prior to index spinal fusion was 9, 000, 968; LESI comprised the largest portion of the total cost of MNT (4, 094, 646, 45.5%), followed by NSAIDS (1, 624, 217, 18.0%) and opioid costs (1, 279, 219, 14.2%). At the patient level, when normalized per patient utilizing therapy, an average 4010 was spent on nonoperative treatments prior to index lumbar surgery. Conclusion: Assuming minimal improvement in pain and functional disability after maximum nonoperative therapies, the incremental cost-effectiveness ratio (ICER) for MNTs could be highly unfavorable. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textIn this retrospective study of 492, 822 adult patients, of which 4133 underwent lumbar decompression and fusion procedures for symptomatic lumbar stenosis or spondylolisthesis, we highlight the increasing costs of long-term maximum nonoperative therapies (MNT). The average cost of MNT over the 5 years prior to surgery was 4010 per patient.